Considerations and strategies in the organisation of obstetric anaesthesia care during the 2019 COVID-19 outbreak in Singapore. (August 2020) - Lee, J.S.E.; Goy, R.W.L.; Sng, B.L.; Lew, E.
Highlights: Identifying 'high-infection risk' parturients is challenging in the COVID-19 outbreak. A multidisciplinary approach is required to provide obstetric anaesthesia services. Protocols for labour analgesia and caesarean delivery allow safe provision of care. Infection control resource management allows for the allocation of finite resources. Organisational changes are required to respond to the COVID-19 outbreak. Abstract: The provision of safe obstetric anaesthesia services is essential during the COVID-19 global outbreak. The identification of the 'high-infection risk' parturient can be challenging especially with the rapidly changing risk criteria for COVID-19 'cases'. A multidisciplinary taskforce is required to review the infection control protocols and workflows for managing the parturient for labour analgesia and for caesarean section in order to minimize infection risk to healthcare staff and other parturients. A constant review of such processes is needed to enhance efficiency and to optimise use of finite resources. Good communication between health officials, institutional leadership and ground staff is essential for the dissemination of information.